Domestic violence against women in Atiq Rahimi's The Patience Stone - Zabihzadeh, Seyedehrobabeh; Hashim, Ruzy Suliza; Chua, Gabriel Clement Chen Wei (Penerbit Universiti Kebangsaan Malaysia, 2015)
Domestic violence against women is a common social ill that destroys thousands of women’s lives worldwide (Khan, 2000). However, the growth of this concern, particularly in developing countries such as Afghanistan, requires more scholarly attention not only because the lives of many Afghan women are affected by it, but also because it remains overlooked due to socio-cultural norms that consider discussions about it as taboo. Of late, however, there is a rising trend among members of the Afghan Diaspora in portraying domestic violence against their womenfolk back home through such artistic mediums as fiction (Parveen, 2015). Therefore, in this paper, we shall examine the manifestations of domestic violence against women in the Afghan context through a textual analysis of The Patience Stone by Atiq Rahimi, an author belonging to the Afghan Diaspora. Originally written in French, this breakthrough novella highlights the harsh reality of the misery suffered by many Afghan women on a regular basis, notably the various forms of domestic violence that they have to endure in the poverty-stricken, war-torn and staunchly patriarchal environment of their homeland. Through a feminist reading of The Patience Stone (2011), we shall examine Rahimi’s depictions of domestic violence against women in the novella as a highly engendered phenomenon resulting from gender inequality and a sexist hierarchy of power prevalent in Afghan society. Furthermore, this paper is outlined based on three main forms of domestic violence, namely physical, sexual and emotional abuse, which are depicted in The Patience Stone through the novella’s female characters, notably the main protagonist.